BRAZILIAN MULTI-SOCIETY POSITION STATEMENT ON EMERGING BARIATRIC AND METABOLIC SURGICAL PROCEDURES - Valezi, Antonio Carlos (2023)
This Brazilian multi-society position statement on emerging bariatric and metabolic surgical procedures was issued by the Brazilian Society of Bariatric and Metabolic Surgery (SBCBM), the Brazilian College of Digestive Surgery (CBCD), and the Brazilian College of Surgeons (CBC). This document is the result of a Brazilian Emerging Surgeries Forum aimed at evaluating the results of surgeries that are not yet listed in the Federal Council of Medicine (CFM), the regulatory agency that oversees and regulates medical practice in Brazil. The Forum integrated more than 400 specialists and academics with extensive knowledge about bariatric and metabolic surgery, representing the three surgical societies: SBCBM, CBC, and CBC. International speakers participated online and presented their experiences with the techniques under discussion, emphasizing the regulatory policies in their countries. The indications for surgery and the subsequent procedures were carefully reviewed, including One Anastomosis Gastric Bypass (OAGB), Single Anastomosis Duodeno-Ileal with Sleeve Gastrectomy (OADS or SADI-S), Sleeve Gastrectomy with Transit Bipartition (SGTB), and Sleeve Gastrectomy with Ileal Interposition (SGII). The recommendations of this document are based on an extensive literature review and discussions among bariatric surgery specialists from the three surgical societies. We concluded that patients with a body mass index (BMI) over 30 kg/m2 may be candidates for metabolic surgery in the presence of comorbidities (arterial hypertension and type 2 diabetes) with no response to clinical treatment of obesity or in the control of other associated diseases. Regarding the surgical procedures, we concluded that OAGB, OADS, and SGTB are associated with low morbidity rates and with satisfactory weight loss and resolution of obesity-related comorbidities such as diabetes and arterial hypertension. SGII was considered a good and viable promising surgical alternative technique. The recommendations of this statement aim to synchronize our societies with the sentiments and understandings of most of our members and also serve as a guide for future decisions regarding bariatric surgical procedures in our country and worldwide.